Characteristics and risk factors of type I or II endoleaks after thoracic endovascular aortic repair and open surgery - Zhu, Fan; Chen, Jia; Guo, Yuanyuan; Shu, Chang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundType I endoleaks (T1ELs) and type II endoleaks (T2ELs) are among the most severe complications that occur after thoracic endovascular aortic repair (TEVAR) and open surgery. This investigation aimed to analyze the predictors and multiple risk factors of T1ELs and T2ELs, with a particular focus on the diameter of the false lumen and the pathology of the left subclavian artery (LSA).MethodsA total of 245 patients (mean age 57 ± 13 years) who had undergone open surgery or TEVAR were recruited and followed for a mean of 18 ± 10 months. Seven patients (2.8%) were classified into the T1EL group, and another seven (2.8%) were classified into the T2EL group. Contrast-enhanced computed tomography angiography of the entire aorta confirmed the diagnosis of aortic disease (e.g., thoracic aortic dissection, thoracic aortic aneurysm, and/or type B intramural hematoma) as well as the presence of T1ELs or T2ELs.ResultsReoperation was more common in the T1EL group (n = 4; 57%) than in the T2EL group (n = 2; 29%); also, reintervention for stenting of the thoracic endovascular graft was more frequent in the T1EL group (4 vs. 1). In T1EL group, four patients (57%) accepted reoperation due to progressive enlargement of the false lumen’s diameter (aneurysm size > 55 mm) (n = 4; 100%) and sharp, persistent chest and back pain (n = 4; 100%). In the T2EL group, two patients (29%) required reintervention due to the false lumen’s growth rate (>5 mm in diameter per half year) and symptoms of pulmonary vascular compression such as hemoptysis and dyspnea (n = 2; 100%). The median survival rate of patients in the T1EL and T2EL groups was 31 months [95% confidence interval (CI) 0.0937–11.4] and 30 months (95% CI: 0.08775–10.67), respectively. The proximal opening angle of the LSA (OR 3.141, 95% CI: 2.615–3.773) was significantly associated with the incidence of T1EL. Both the proximal opening angle of the LSA and its diameter were significantly associated with the occurrence of T2ELs.ConclusionsTo prevent the occurrence of T1ELs and T2ELs, appropriate stent grafts and the pathology of the LSA should be carefully considered.